Realm of Malay Civilization: Ethnoparenting, Habitus, and Cultural Contestation in Early Childhood Education of Sambas Malay Society - Suratman, Bayu; Arif, Mahmud (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2020)
This article discusses how Sambas Malay parents carry out ethnoparenting and early childhood education to early childhood. Sambas Malay society are relatively traditional who still maintain the value system embraced by the local community. Ethnoparenting in this paper has the meaning of parenting performed by a particular ethnicity or tribe through the culture adopted. This research was conducted by the qualitative method through a sociological approach to education. The data was obtained through interviews and in-depth observations in Batu Makjage Village, Tebas District, Sambas Regency, West Kalimantan Province. Some habitus in ethnoparenting Sambas Malay society in educating early childhood includeÂ tunjuk ajar, pantang larang, kemponan and any tradition. Obstacles in ethnoparenting in the form of contestation of the value of Sambas Malay culture with modernity. The contestation that occurred experienced dislocation and resulted in the social change of Sambas Malay society and changed the habitus and urban lifestyle that has dominated in the ethnoparenting of Sambas Malay society.